Stronger shared taste for natural aesthetic domains than for artifacts of human culture - Vessel, Edward A.; Maurer, Natalia; Denker, Alexander H.; Starr, G. Gabrielle (Cognition, 2018)
•Aesthetic judgments of faces and natural landscapes show high “shared taste.”•Aesthetic judgments of paintings and architecture vary more across individuals.•Observers show similar test-retest reliability for all domains. Individuals can be aesthetically engaged by a diverse array of visual experiences (paintings, mountain vistas, etc.), yet the processes that support this fundamental mode of interaction with the world are poorly understood. We tested whether there are systematic differences in the degree of shared taste across visual aesthetic domains. In Experiment 1, preferences were measured for five different visual aesthetic domains using a between-subjects design. The degree of agreement amongst participants differed by domain, with preferences for images of faces and landscapes containing a high proportion of shared taste, while preferences for images of exterior architecture, interior architecture and artworks reflected strong individual differences. Experiment 2 used a more powerful within-subjects design to compare the two most well matched domains—natural landscapes and exterior architecture. Agreement across individuals was significantly higher for natural landscapes than exterior architecture, with no differences in reliability. These results show that the degree of shared versus individual aesthetic preference differs systematically across visual domains, even for photographic images of real-world content. The findings suggest that the distinction between naturally occurring domains (e.g. faces and landscape) versus artifacts of human culture (e.g. architecture and artwork) is a general organizational principle governing the presence of shared aesthetic taste. We suggest that the behavioral relevance of naturally occurring domains results in information processing, and hence aesthetic experience, that is highly conserved across individuals; artifacts of human culture, which lack uniform behavioral relevance for most individuals, require the use of more individual aesthetic sensibilities that reflect varying experiences and different sources of information.